Geochemistry characterization of organic soil - Tiong, Kenny Ping Chiet (2010)
The behaviour of organic soil was found to be governed by its chemical properties rather than its physical properties. Hence, it is important to determine the geochemistry properties of organic soils besides its physical properties. The main objective of this study was to characterize the geochemistry properties of organic soils for civil engineering applications. The organic soil specimens were retrieved from three different locations at Batu Pahat, Johor, namely Parit Nipah, Parit Sidek and Batu Puteh using peat auger and undisturbed sampler. The top layer of the peat soil which is rich in non-humified matters was excluded from this study. The geochemistry properties of the organic soils underneath the peat soil were determined through laboratory tests; Total Organic Carbon (TOC), Loss of Ignition (LOI) and etc. Besides it, this study also highlighted the correlation of geochemistry properties of organic soils with its physical behaviors namely strength, moisture content, specific gravity, and Atterberg limits. This study provided a good understanding of organic soils which enable the designer to identify and investigate the effect of geochemical properties towards the soil behaviour.